1990
DOI: 10.1620/tjem.160.167
|View full text |Cite
|
Sign up to set email alerts
|

Co-mutagenic activity of phenoxyherbicides MCPA- and MCPB-ethylester in the Ames assay.

Abstract: S., MAGARA, J. and YAMAMOTO, M. Co-Mutagenic Activity of Phenoxyherbicides MCPA-and MCPB-Ethylester in the Ames Assay. Tohoku J. Exp. Med., 1990, 160 (2), [167][168] Mutagenicity and co-mutagenicity of MCPA-and MCPB-ethylester were examined in the Ames assay. It was found that they enhance the mutagenic action of 2-aminoanthracene in the Ames assay, although they were not mutagenic.phenoxyherbicides ; MCPA-and MCPB-ethylester ; Ames assayIn spite of the extensive use of the phenoxyherbicides, 4-chloro-2-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Although it has been reported that MCPA, a chlorinated phenoxyacid compound, is not mutagenic (Moriya et al 1983) but has co-mutagenic activity in Ames assay (Shibuya et al 1990), adequate data to evaluate the carcinogenicity of MCPA are not available in any experimental animals and humans (IARC 1983). However, Hardell and Sandstrom (1979), and Moses and Selikoff (1981) suggested that phenoxy acid compounds were related to increased incidence of soft tissue sarcomas in the epidemiological studies.…”
mentioning
confidence: 99%
“…Although it has been reported that MCPA, a chlorinated phenoxyacid compound, is not mutagenic (Moriya et al 1983) but has co-mutagenic activity in Ames assay (Shibuya et al 1990), adequate data to evaluate the carcinogenicity of MCPA are not available in any experimental animals and humans (IARC 1983). However, Hardell and Sandstrom (1979), and Moses and Selikoff (1981) suggested that phenoxy acid compounds were related to increased incidence of soft tissue sarcomas in the epidemiological studies.…”
mentioning
confidence: 99%
“…Some investigators have found evidence suggesting that these compounds are related to an increased incidence of soft tissue sarcomas in epidemiological studies (Hardell and Sandstrom 1979;Moses and Selikoff 1981). MCPA is not mutagenic (Moriya et al 1983;IARC 1983), but it amplifies growth inhibition originally induced by mitomycin C (Yamamoto et al 1988b), and enhances the mutagenicity of 2-aminoanthracene (Shibuya et al 1990). A phenoxyacid herbicide, 2, 4-dichlorophenoxyacetic acid (2, 4-D), is not mutagenic in the Ames test, but may be carcinogenic in experimental animals (Reuber 1983).…”
mentioning
confidence: 99%
“…Yamamoto et al analyzed the statistical correlation between agricultural chemicals and standardized mortality ratios (SMRs) for death from BTC and found that the use of ethyl 4-chloro-2-methylphenoxyacetate (MCPA), a phenoxyacid herbicide, was significantly correlated with the SMRs. MCPA itself is not mutagenic (Moriya et al 1983) but has co-mutagenic action (Yamamoto et al 1988 ;Shibuya et al 1990). MCPA has not only the inductive effect on hepatic xenobiotic metabolizing enzymes ) but also the proliferative action of hepatic peroxisome.…”
mentioning
confidence: 99%